Awareness Regarding Health Promotion of Infants among Mothers of Rupandehi, Nepal - Lamichhane, Kavita; Maharjan, Swetha; Kachapati, Anuja (Journal of Universal College of Medical Sciences, 2020)
INTRODUCTION: Health promotion of infancy is necessary for the optimum growth and development. Mother is significant person for the promotion of health of infant.MATERIAL AND METHODS: Descriptive cross-sectional study was conducted to find out the awareness regarding health promotion of infants among 78 mothers in Bhim Hospital of Siddharthanagar Municipality by using purposive sampling technique. Semi- structured interview schedule was used to collect data and analyzed by using descriptive and inferential statistics with SPSS version 20.RESULTS: The study findings revealed that 51.3% of the respondents have low level of awareness regarding health promotion of an infant. There was statistically significant association between respondents’ level of awareness with occupation and respondents’ husband’s age.CONCLUSION: The study concluded that more than half of the mothers have low level of the awareness regarding health promotion of the infant. Mothers’ occupation and husbands’ age are the influencing factors on mothers' knowledge regarding health promotion of infant.